Geschlechterverhältnisse im Kontext von Unternehmen und Gesellschaft: - Carl, Andrea-Hilla; Kunze, Stefanie; Olteanu, Yasmin; Yildiz, Özlem; Yollu-Tok, Aysel (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
Claudia Gather, feminist, researcher, networker, mentor, professor and tireless political influencer, has left a lasting impression in recent decades through her work, thinking and actions, not only on the field of gender studies in terms of research, teaching and practice but also on those people she has supported carefully and without question over the years. This is reason enough to dedicate an anniversary publication which honours her academic life work to her. This anniversary publication assembles articles on the topics of work, entrepreneurship, power and sustainability contributed by her long-time friends and colleagues. All of them critically discuss pathways for more gender equality and pluralism in academia and society in each respective context.With contributions byPhilipp Kenel; Irem Güney-Frahm; Tanja Fendel, Özlem Yildiz; Tanja Schmidt; Stefanie Kunze, Mirko Bendig; Yasmin Olteanu; Lena Schürmann; Ulrike Marx, Albrecht Becker; Bouchra Achoumrar; Thomas Afflerbach, Katharina Gläsener; Anna Kasten, Kerstin Raule; Katharina Gapp-Schmeling, Anneli Heinrich; Anna Brüning-Pfeiffer; Sabine Hark, Friederike Maier.